Implementation of Religious Education for Early Childhood : A Case Study in a Multicultural Kindergarten - Saputri, Nurul; Sirait, Nilna Mayang Kencana (Universitas Islam Negeri Sumatera Utara, 2025)
The purpose of this research is to examine the importance of the implementation of religious education in early childhood at Kartika Ayu PTPN IV Kebun Mayang Kindergarten, Bosar Maligas District, Simalungun Regency. Religious education is implemented with an inclusive approach, given the diverse religious backgrounds of the students. The research method used is qualitative with a case study approach, which includes observation, interviews and document analysis. The research subjects consisted of children, teachers and parents. The results showed that religious education at Kartika Ayu Kindergarten is implemented regularly, with lessons held every Friday. Various methods such as singing, storytelling and games are used in teaching, which proved effective in attracting children's attention and helping them understand religious values. The benefits of this research based on interviews with teachers, students and parents revealed that they highly appreciate this religious education program, which not only improves children's religious knowledge but also builds character and tolerance. The findings from this study are expected to serve as a reference for other educational institutions in implementing effective religious education.